Utilization of Phosphogypsum and Sediment in Subgrade Material for Pavement Construction - Dragana Tomašević Pilipović; Nataša Slijepčević; Dunja Rađenović Veselić; Miloš Šešlija; Vesna Bulatović; Nataša Duduković (Applied Sciences)
(1) Background: The construction industry continuously seeks sustainable alternatives to traditional materials for subgrade material in pavement construction, aiming to mitigate environmental impact while maintaining performance standards. This study investigates the feasibility of incorporating phosphogypsum (PG) and contaminated sediment into subgrade materials, focusing on their physico-chemical and physico-mechanical properties. (2) Methods: The physico-chemical and physico-mechanical properties, performance, and mechanisms of solidified sediment with phosphogypsum (3% and 5% of phosphogypsum in mixture) were studied using long-term leaching tests (ANS 16.1), uniaxial compressive strength (UCS), California Bearing Ratio (CBR), X-ray fluorescence (XRF), and thermogravimetric analysis (TGA). (3) Results: Based on the pseudo-total metal content (Cr, Ni, Cu, Zn, As, Cd, Pb), the sediment is classified as third- and fourth-class, indicating it is polluted and requires treatment before disposal in the environment. To assess the long-term behavior of the sediment treated with phosphogypsum (S/S), a semi-dynamic ANS 16.1 leaching test was performed. The results showed that the metals exhibit moderate mobility, with average diffusion coefficients (De) ranging from 10−8 cm2/s for Zn (in both mixtures) to 10−12 cm2/s for Cr (in mixture F-3). The leaching index (LX) values for both mixtures were above 9 for most metals, confirming their suitability for “controlled” use. Granulometric analysis indicated a predominance of fine particles, which enhances the material’s plasticity and mechanical properties. Atterberg consistency tests showed that increasing phosphogypsum content improved both the Liquid Limit and Plastic Index. However, UCS tests indicated that neither the 3% nor 5% phosphogypsum mixtures met the minimum strength requirements for subgrade material. On the other hand, CBR values demonstrated promising performance, with 12.5% for the 3% phosphogypsum mixture and 22.9% for the 5% phosphogypsum mixture. Overall, phosphogypsum positively influenced the strength development of the sediment-PG mixtures, as confirmed by XRF and TGA analyses. (4) Conclusions: Environmental considerations, such as leachability of contaminants, were investigated to ensure the sustainability of the proposed subgrade materials. Leaching tests indicated minimal pollutant release, suggesting the potential for safe utilization of PG and sediment in subgrade material. This study provides valuable insights into the physico-chemical and physico-mechanical properties of pavement mixes incorporating PG and sediment, supporting the feasibility of using these alternative materials in sustainable subgrade material for pavement construction and offering a viable solution to mitigate waste generation while enhancing pavement performance.